The effectiveness of acceptance and commitment therapy on perception of suffering, resilience and sexual self-respect of betrayed women - Sabaghpoor Azarian, Sajedeh; Nouri, Nasim (Psychology of Woman Journal, 2022)
This study was conducted with the aim of investigating the effectiveness of acceptance and commitment therapy on the perception of suffering, resilience and sexual self-esteem of betrayed women. The research method was quasi-experimental with a pre-test-post-test design with a control group. The statistical population included available women who had experienced infidelity and referred to psychological clinics in the sixth regions of Tehran, from this group, thirty people were selected in a non-random way and were randomly divided into two equal groups, in the experimental and control groups. Eight treatment sessions were performed in ninety minutes and at the end, the post-test was performed in both groups. The research instruments included the Suffering Perception Scale (2010), Resilience Scale (2003) and Women's Sexual esteem Questionnaire - Short Form (1966). For data analysis, the statistical method of covariance analysis was used. The findings revealed that the acceptance and commitment therapy is significantly effective in reducing the perception of suffering and increasing resilience and sexual self-esteem of betrayed women. the results of this research can be used in the field of therapy injury caused by betrayal in women.